2016
DOI: 10.1007/s11665-016-2140-2
|View full text |Cite
|
Sign up to set email alerts
|

Electropolishing of Re-melted SLM Stainless Steel 316L Parts Using Deep Eutectic Solvents: 3 × 3 Full Factorial Design

Abstract: SummaryThis three levels three factors full factorial study describes the effects of electropolishing using deep eutectic solvents on the surface roughness of re-melted 316L stainless steel samples produced by the Selective Laser Melting (SLM) powder bed fusion additive manufacturing method. An improvement in the surface finish of re-melted stainless steel 316L parts was achieved by optimizing the processing parameters for a relatively environmentally friendly ('green') electropolishing process using a Choline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(22 citation statements)
references
References 26 publications
0
22
0
Order By: Relevance
“…), [163][164][165][166][167][168][169][170][171][172][173][174] and chemical and electrochemical polishing. [175][176][177] Schaller, et al, showed that industrial silica grit blasting used to knock off partially fused powder caused active corrosion of SLM 304L at open circuit in quiescent 0.6 M NaCl. 101 They attributed this to incomplete removal of surface voids, high imparted strain, and embedded silica particles in the matrix.…”
Section: Surface Finishingmentioning
confidence: 99%
“…), [163][164][165][166][167][168][169][170][171][172][173][174] and chemical and electrochemical polishing. [175][176][177] Schaller, et al, showed that industrial silica grit blasting used to knock off partially fused powder caused active corrosion of SLM 304L at open circuit in quiescent 0.6 M NaCl. 101 They attributed this to incomplete removal of surface voids, high imparted strain, and embedded silica particles in the matrix.…”
Section: Surface Finishingmentioning
confidence: 99%
“…Trelewicz et al indicated that the corrosion resistance of SLM-processed 316L steel was reduced because of the inhomogeneous solute distribution [ 17 ]. Due to the worse mechanical properties of SLM-produced elements, numerous studies are being conducted related to process parameter modification [ 18 , 19 , 20 ], in-process material annealing using laser re-melting [ 21 , 22 ], or post-process heat treatment [ 23 , 24 ]. All mentioned sources indicate the possibility of improvement of the mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…The temperature increase results in an exponential increase of current density and affects the electrochemical reactions [19]. A study on EP of re-melted LPBF 316L stainless-steel using ILs [23] showed that at very high electrolyte temperatures, the material dissolution and surface roughness increase due to an increased current density, which may result in a non-homogeneous material dissolution. As shown in Figure 3, the current density plateau increases as the temperature increases from 25 to 50 °C.…”
Section: Ep Optimization and Polishing Mechanismsmentioning
confidence: 99%
“…The passivation mechanism is limited by the diffusion of acceptor anions to the dissolving metal The temperature increase results in an exponential increase of current density and affects the electrochemical reactions [19]. A study on EP of re-melted LPBF 316L stainless-steel using ILs [23] showed that at very high electrolyte temperatures, the material dissolution and surface roughness increase due to an increased current density, which may result in a non-homogeneous material dissolution. As shown in Figure 3, the current density plateau increases as the temperature increases from 25 to 50 • C. In addition, the temperature increase also intensifies the chemical reactions related to the super-saturation of the salt film in the i-peak region by increasing the value of the current density peak.…”
Section: Ep Optimization and Polishing Mechanismsmentioning
confidence: 99%